Mineralogy and texture of the iron ore deposits in Tanjung and Pake, Bontocani, South Sulawesi, Indonesia. Issue 1 (1st January 2023) - Bakri, H; Imran, A M; Maulana, A; Irfan, U R
Abstract: Iron ore deposits in the Bontocani area are scattered in the form of boulders around the contact zone between granodiorite and limestone, which indicates the skarn type. The study of mineralogy, particularly Fe-bearing minerals in outcrops in the Tanjung and Pake areas, is the goal of this research. The method chosen is fieldwork for detailed analysis of characteristics and relationships between granodiorite intrusions and limestones, as well as representative rock sampling. Furthermore, mineralogy analysis in the laboratory using ore petrography and XRD (X-Ray Diffraction) methods. The iron-bearing minerals found at both of their locations consisted of oxides namely magnetic, hematite, and ilmenite; hydroxide minerals namely goethite; and siderite of the carbonate group. In the Tanjung area as well-found sulfide minerals, namely pyrite, chalcopyrite, covellite, and sphalerite; chromite and manganese of the oxide-hydroxide group; and gangue minerals consisting of calcite, quartz, albite, diopside, hedenbergite, danalite, andradite, and magnesite. Meanwhile, in Pake, the sulfide minerals found are alabandite; oxide minerals namely manganese and pyrolusite; azurite from the hydroxide group; and gangue minerals including calcite, quartz, magnesite, chlorite, andradite. Based on the mineral texture of the ore from mineragraphic analysis, there are textures in the form of open space-filling, replacement, intergrowth, and granular.